2004
DOI: 10.3402/ijch.v63i0.17909
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of perinatal care in Inukjuak, Nunavik, Canada 1998–2002

Abstract: Three out of four women can stay in Inukjuak and give birth with a PMR of 0.7%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…Before the establishment of the midwifery service in 1986, 91 percent of Hudson coast women were evacuated to hospitals outside Nunavik. Our work supports previous findings that most women served by the Inuulitsivik midwives are able to birth safely in Nunavik .…”
Section: Discussionsupporting
confidence: 91%
“…Before the establishment of the midwifery service in 1986, 91 percent of Hudson coast women were evacuated to hospitals outside Nunavik. Our work supports previous findings that most women served by the Inuulitsivik midwives are able to birth safely in Nunavik .…”
Section: Discussionsupporting
confidence: 91%
“…The programme has been a resounding success (Van Wagner et al. 2007, 390–1), with perinatal outcomes that match or exceed southern norms (Houd, Qinuajuak, and Epoo 2004, 239–41). Inuit midwives now conduct most births, although southern midwives continue to form an important part of the staff, and the Maternity has now become the Inuulitsivik Maternities as further branches have been established in Inukjuak and Salluit (Pauktuutit 1990).…”
Section: Challenge To the Biomedical Hierarchymentioning
confidence: 99%
“…Birthing services should be located as close to the woman's home as possible. International evidence has shown that birthing services can be provided safely in very remote settings [54][55][56]. It is time to rethink the closure of rural and remote birthing services that is currently occurring across Australia without adequate application of evidence or evaluation.…”
Section: A Way Forwardmentioning
confidence: 99%